Balancing Inflammation: Computational Design of Small-Molecule Toll-like Receptor Modulators. (February 2017) - Murgueitio, Manuela S.; Rakers, Christin; Frank, Anne; Wolber, Gerhard
Abstract : As essential proteins of the innate immune system, Toll-like receptors (TLRs) are involved in a plethora of physiological pathologies and their modulation is an ongoing quest in the field of drug discovery. Although TLRs recognize an unusually broad range of different molecular patterns, only a few small-molecule TLR modulators have been reported to date. Recent advances in crystallography and in silico techniques provide promising opportunities for TLR investigations and drug design. Here, three application areas for computational approaches are considered: (i) exploration of TLR structure and activation; (ii) understanding TLR modulation; and (iii) TLR drug discovery. By providing an overview on state-of-the-art computational methods, we highlight the value of molecular modeling in mechanistically understanding TLR function and guiding drug design. Trends: TLRs play a crucial role in the activation of innate immune response and have been suggested as drug targets for the treatment of several diseases linked to inflammation. Recently the X-ray structures of several TLRs in ligand-bound and unbound states have been resolved, providing deep insights into the structure and function of the receptors. Computer-aided-drug design promises to render the discovery and development of TLR modulators more rational and efficient. Computational tools are mainly used to investigate the structure and function of the receptors, to understand the modulation mechanisms through known modulators and to discover and develop novel lead structures through virtual screening.